Political Aid Cycles - Faye, Michael; Niehaus, Paul (American Economic Review, 2012)
Researchers have scrutinized foreign aid's effects on poverty and growth, but anecdotal evidence suggests that donors often use aid for other ends. We test whether donors use bilateral aid to influence elections in developing countries. We find that recipient country administrations closely aligned with a donor receive more aid during election years, while those less aligned receive less. Consistent with our interpretation, this effect holds only in competitive elections, is absent in US aid flows to non-government entities, and is driven by bilateral alignment rather than incumbent characteristics.